Development of a plant-made immunoassay for the detection of Porcine circovirus infections in South African swine herds - Angobe, Aune Tuyoleni (Department of Molecular and Cell Biology, 2021)
Porcine circovirus type 2 (PCV-2) is considered the major cause of porcine circovirusassociated diseases and is one of the major pathogens in swine producing countries. PCV-2 is a non-enveloped virus with a single stranded circular DNA genome of about 1.8 kb. This encodes the single capsid protein (CP) which is highly immunogenic, as well as a replication-associated protein. Recombinantly expressed CP can selfassemble into virus-like particles (VLPs) that are structurally and immunogenically very similar to native virions. Current commercially available diagnostic kits are VLPbased and are effective at detecting PCV-2 antibodies in sera. However, these diagnostic assays are expensive, therefore limiting their use in developing countries. Plant-based transient expression systems have recently been investigated to express PCV-2 CP for a cheaper diagnostic reagent. The aim of this study was to develop an inexpensive lateral flow device to be able to test for PCV infection in pig herds. Production of PCV-2 CP in Nicotiana benthamiana via transient Agrobacterium-mediated expression was optimised by comparing two expression vectors, pEAQ-HT and pCBP2, and VLPs were also expressed in Escherichia coli. VLPs produced in plants and in E. coli were used to set up a lateral flow device. In addition, various purification methods of VLPs such as ion exchange chromatography (IEC) and sucrose gradient ultracentrifugation were explored to obtain pure VLPs free of bacterial contamination. The VLPs were successfully expressed in N. benthamiana with both pEAQ-HT and pCBP2, and VLPs were subsequently purified on discontinuous sucrose gradients by ultracentrifugation. The assembly of the CP was assessed by transmission electron microscopy, which showed the presence of assembled VLPs. To further purify the VLPs IEC was used, and fully assembled VLPs which were free of contamination were prepared. Purified VLPs expressed in plants and E. coli were successfully used as coating antigen in lateral flow devices, which were able to detect PCV-2 CP antibodies in CP-immunised rabbit sera. E. coli-made VLPs showed higher affinity to PCV-2 antibodies compared to plant-made VLPs. In conclusion, this study has successfully demonstrated the potential to use a plantbased transient expression system to produce affordable diagnostic reagent, especially for developing countries. This is the first study that expressed PCV-2 VLPs using a pCBP-2 expression vector and used PCV-2 VLPs as a coating reagent in the development of a lateral flow test as a proof of concept.